KEPEMIMPINAN VISIONER DALAM PERSPEKTIF ISLAM - BUDIMAN, HARIS (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2017)
The Visionary Leadership is its significant role to improve the institution is including in educational institution. The Visionary Leadership is one of leadership is considered to increase the educational quality today. The Visionary Leadership is the model of leadership is convinced more of human being as it to carry out the future modernity in the Islamic educational institution. Because, this model is its the biggest competency to know, to get the attitude and to get the response of modernity era. According to the Holy Koran and Hadis Rasulullah SAW can be conclusion that the Visionary Leadership in Islamic Perspective is the guidance activity and making reference to God blessing. Key Word: Visionary Leadership, Islamic Perspective